2018
DOI: 10.1016/j.quascirev.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic influences on late Holocene relative sea levels from the central-eastern Adriatic coast of Croatia

Abstract: Differential tectonic activity is a key factor responsible for variable relative sea-level (RSL) changes during the late Holocene in the Adriatic. Here, we compare reconstructions of RSL from the central-eastern Adriatic coast of Croatia with ICE-7G_NA (VM7) glacial-isostatic model RSL predictions to assess underlying driving mechanisms of RSL change during the past~2700 years. Local standardized published sea-level index points (n ¼ 23) were combined with a new salt-marsh RSL reconstruction and tide-gauge mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…Bonaldo et al (2020) also showed a shift in directional wave-energy contributions in the northern Adriatic resulting in a possible local increase in wave climate severity along the northern and north-eastern coasts. This process could be aggravated in northern Croatia by coastal subsidence amounting to 0.4 mm per year (Faivre et al, 2019a(Faivre et al, , 2021, which is coherent with the estimated 0.45±0.6 mm per year subsidence in southern Croatia (Faivre et al, 2013;Shaw et al, 2018). Moreover, RSL changes for the last 1500 years along north-eastern coasts seem consistent with shifts in temperature and consequently with periods of rapid climate change (Faivre et al, 2019a).…”
Section: Introductionsupporting
confidence: 73%
“…Bonaldo et al (2020) also showed a shift in directional wave-energy contributions in the northern Adriatic resulting in a possible local increase in wave climate severity along the northern and north-eastern coasts. This process could be aggravated in northern Croatia by coastal subsidence amounting to 0.4 mm per year (Faivre et al, 2019a(Faivre et al, , 2021, which is coherent with the estimated 0.45±0.6 mm per year subsidence in southern Croatia (Faivre et al, 2013;Shaw et al, 2018). Moreover, RSL changes for the last 1500 years along north-eastern coasts seem consistent with shifts in temperature and consequently with periods of rapid climate change (Faivre et al, 2019a).…”
Section: Introductionsupporting
confidence: 73%
“…The northern Adriatic coast is generally considered to be a subsiding environment (Pirazzoli, 2005;Antonioli et al, , 2007Shaw et al, 2018). In order to estimate the ongoing contribution of land-level change and identify climate driven sealevel trends, we applied corrections for crustal movements associated with the spatially variable and ongoing GIA.…”
Section: Vertical Land Motionmentioning
confidence: 99%
“…This quantitative approach has been used in several recent papers dealing with RSL change (e.g. Kemp et al, 2011Kemp et al, , 2013Shaw et al, 2018) providing data which can further be reliably compared (e.g. Kemp et al, 2015).…”
Section: Quantitative Analyses Of Relative Sea-level Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2274 individual data points in the database use proxies such as foraminifera, diatoms, testate amoebae, coral microatolls, archaeological evidence, and sediment geochemistry. We have updated the database (Supplementary Data) from Kemp et al (2018) to include 390 new RSL data points from northern New Jersey, USA (this study); Croatia 56 ; French Polynesia 57 ; Israel 58 ; Quebec 59 ; Connecticut 25 ; Maine 25 ; and Nova Scotia 25 . We compared the new northern New Jersey record with other published records along the U.S. Atlantic coast from southern New Jersey (Leeds Point and Cape May Courthouse 14 ), New York City 15 , Connecticut 60 , and North Carolina 45 to examine regional variability in magnitudes and rates of past RSL change, as well as variability in regional Common Era sea-level budgets.…”
Section: Methodsmentioning
confidence: 99%